An Absolutist Theory of Faultless Disagreement in Aesthetics. (29th September 2015) - Baker, Carl; Robson, Jon
Abstract: Some philosophers writing on the possibility of faultless disagreement have argued that the only way to account for the intuition that there could be disagreements which are faultless in every sense is to accept a relativistic semantics. In this article we demonstrate that this view is mistaken by constructing an absolutist semantics for a particular domain – aesthetic discourse – which allows for the possibility of genuinely faultless disagreements. We argue that this position (Humean absolutism) is an improvement over previous absolutist responses to the relativist's challenge and that it presents an independently plausible account of the semantics of aesthetic discourse.